2019
DOI: 10.1038/s41598-019-54311-x
|View full text |Cite
|
Sign up to set email alerts
|

Light therapy with boxes or glasses to counteract effects of acute sleep deprivation

Abstract: Sleep deprivation, in the context of shift work, is an increasing major public health issue. We aimed to determine whether early light administration can counteract sleep deprivation effects, and to compare LED-glasses with a traditional light therapy box. This cross-over design study included 18 individuals exposed to light therapy for 30 minutes at 5 am after one night of complete sleep deprivation, to mimic the night shift condition. Individuals were randomly exposed to 10,000 Lux light box, 2,000 Lux LED b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
1
21
0
1
Order By: Relevance
“…Light also acts on the sleep homeostasis process by increasing the sleep intensity [ 69 ]. In addition, it has been demonstrated that LT increases alertness [ 70 ], including after a night of sleep deprivation and a morning exposition to LT [ 71 ]. LT has also been shown to improve sleepiness and sustained attention, among other cognitive functions [ 67 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Light also acts on the sleep homeostasis process by increasing the sleep intensity [ 69 ]. In addition, it has been demonstrated that LT increases alertness [ 70 ], including after a night of sleep deprivation and a morning exposition to LT [ 71 ]. LT has also been shown to improve sleepiness and sustained attention, among other cognitive functions [ 67 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…CBT + comprised one 60-minute face-to-face session at the PMCC Chemotherapy Day Unit; one 20-minute telephone call at study mid-point and seven, weekly CBT-I content emails. Light boxes and glasses produce comparable effects 38 . Participants wore Luminette® light glasses for 20 minutes (per manufacturer recommendation) each morning at the brightest setting (see Supplementary methods).…”
Section: Methodsmentioning
confidence: 99%
“…The SCN mainly receives light signals, so the optimization of daily light exposure can be used to increase circadian synchrony [ 118 ]. Bright light in the morning (bright light therapy, BLT) has been used as a treatment for mood disorders, depression and circadian abnormalities, including shift work and sleep disorders [ 119 , 120 ]. High-intensity light exposure daily in the morning contributed to the proper function of the circadian system and, therefore, lowered body weight and improved glucose tolerance in sand rats [ 121 ].…”
Section: Treatment For T2dm and Ad Targeting Circadian Rhythmsmentioning
confidence: 99%